PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KARTU SIMPATI DI KOTA JAMBI - Risma Amelia Irani (Jurnal Manajemen Terapan dan Keuangan, 2019)
Advertising is to influence purchases. This research aims to analyze the influence of advertising and brand image of card simpati, either partially or simultaneous. The methods used in this research is quantitative with the survey. The number of samples is 97 respondents. Methods of analysis used was multiple linear regression. Advertising and brand image gives a strong influence of Simpati card purchases in the city of Jambi. The test results of the analysis that has been done, on the test simultaneously replied that the advertising and brand image simultaneously positive and signifivant effect against the purchasing decision. Then in partially test, two variables in this study partially equally influence purchasing decisions.